Percepção ambiental dos usuários do Centro de Pesquisas e Conservação da Natureza Pró-Mata - PUCRS - Muhle, Rita Paradeda (2014)
The Centre for Research and Conservation of Nature Pro-Mata is a private protected area belonging to PUCRS, located in São Francisco de Paula (RS). The place has great scenic beauty in its more than 3000 hectares and its primary purpose is the conservation and environmental research. Welcomes groups of students, teachers and researchers of the university and other accredited universities, and is currently initiating a process of expanding its activities. The opening of the site for different users such as students of Basic Education of São Francisco de Paula and staff PUCRS is diversifying the use of space and demonstrate its possibilities. This research aims to identify and analyze the environmental perception of nine different groups that attended the site between November 2012 and October 2013. Moreover, it is also proposed to identify the potential of the Pro-Mata through the perception of its members, and to draw attention of those responsible for capacity Pro-Mata acting in formation (Bildung) of the subjects who attend there and so contribute with goals the University to be a greener campus and be a local training of individuals responsible, environmentally engaged. Through the application and analysis of open questionnaires and participant observation in each group, it was possible to attest that besides the ability to meet the expectations of the educational proposals of the groups, and to be a place that provides multiple person-environment interactions, the Pro-Mata allows the experience of a sensitizing aesthetic experience that awakens the will to act on behalf of the environment and the next and can also awaken new spirituality. Environmental education must try to awaken a human being who perceives life beyond rationality of science. The aesthetic experience can offer to the education the overcome of the extreme rationalization imposed by the consolidation of modern thought that has weakened the poetic and the imaginary, in that it is capable of awakening an ethic built by openness to experiences of being in the world, recognizing the symmetry between humans and nonhumans and the overcoming of individualism.